Multimedia Learning Design for Ablution and Prayer (Case Studies at Pesantren Arafah Kota Sungai Penuh) (International Journal of Engineering and Computer Science, 2018)
Pesantren Arafah Kota Sungai Penuh is a boarding school attached to Islamization, where every student is required to be able to perform the prayer properly and correctly. With the current teaching-learning process, while teacher still using gestures or still using whiteboards and markers as a medium of learning, so students tend to get bored and difficult to understand, memorize and learn that is taught by the teacher. This research was conducted to make the application related to the obligatory multimedia-based prayer guidance, so that students are easier to remember, understand and study the prayer guidance. The methods used in making this application include; analyze the problem, make designing, make the application program using Macomedia flash 8 software ends by testing. This app consists of three most important parts. First, the input contains the data required in this application. Second, the file that serves as a liaison between the flash and then the data will be displayed into the flash. And third, is making the application on flash as the end of this application. From the results of application testing mandatory prayer-based multimedia can be obtained that by using this application students learn more easily to understand a material. With the construction of multimedia-based applications is expected to increase student motivation in learning and can be easy to memorize, understand and study the mandatory prayer guidance.